Plant Microbiome and Its Link to Plant Health: Host Species, Organs and Pseudomonas syringae pv. actinidiae Infection Shaping Bacterial Phyllosphere Communities of Kiwifruit Plants - Purahong, Witoon; Orrù, Luigi; Donati, Irene; Perpetuini, Giorgia; Cellini, Antonio; Lamontanara, Antonella; Michelotti, Vania; Tacconi, Gianni; Spinelli, Francesco (Frontiers in Plant Science, 2018)
Pseudomonas syringae pv. actinidiae (Psa) is the causal agent of the bacterial canker, the most devastating disease of kiwifruit vines. Before entering the host tissues, this pathogen needs an epiphytic growth phase on kiwifruit flowers and leaves, thus the ecological interactions within epiphytic bacterial community may greatly influence the onset of the infection process. The bacterial community associated to the two most important cultivated kiwifruit species, Actinidia chinensis and Actinidia deliciosa, was described both on flowers and leaves using Illumina massive parallel sequencing of the V3 and V4 variable regions of the 16S rRNA gene. In addition, the effect of plant infection by Psa on the epiphytic bacterial community structure and biodiversity was investigated. Psa infection affected the phyllosphere microbiome structures in both species, however, its impact was more pronounced on A. deliciosa leaves, where a drastic drop in microbial biodiversity was observed. Furthermore, we also showed that Psa was always present in syndemic association with Pseudomonas syringae pv. syringae and Pseudomonas viridiflava, two other kiwifruit pathogens, suggesting the establishment of a pathogenic consortium leading to a higher pathogenesis capacity. Finally, the analyses of the dynamics of bacterial population provided useful information for the screening and selection of potential biocontrol agents against Psa.